2020
DOI: 10.1142/s0219024920500260
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Information Flows in Financial Markets

Abstract: We model continuous-time information flows generated by a number of information sources that switch on and off at random times. By modulating a multi-dimensional Lévy random bridge over a random point field, our framework relates the discovery of relevant new information sources to jumps in conditional expectation martingales. In the canonical Brownian random bridge case, we show that the underlying measure-valued process follows jump-diffusion dynamics, where the jumps are governed by information switches. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…activation and deactivation) of individual signals-is beyond the scope of this work. However, interested readers are referred to Hoyle et al 7 for a detailed yet theoretically demanding exposition. In summary, the dynamics of the conditional expectation process is found to be a jump-diffusion where jumps arise naturally from the activation and deactivation of different individual signals over the trading horizon.…”
Section: The Signal Process and Mutual Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…activation and deactivation) of individual signals-is beyond the scope of this work. However, interested readers are referred to Hoyle et al 7 for a detailed yet theoretically demanding exposition. In summary, the dynamics of the conditional expectation process is found to be a jump-diffusion where jumps arise naturally from the activation and deactivation of different individual signals over the trading horizon.…”
Section: The Signal Process and Mutual Learningmentioning
confidence: 99%
“…Similar to Aydin 6 and Hoyle et al, 7 we now introduce an F i t -adapted stopping time u ij t which keeps track of the most recent time up to the auction time t and there was a trade interaction between agents i and j, that is as follows:…”
Section: Learning Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting models are finely tuned to the structures of the assets that they represent, and therefore offer scope for a useful approach to financial risk management. In previous work on information-based asset pricing, where precise definitions can be found that expand upon the ideas summarized above, such models have been constructed using Brownian bridge information processes (Brody et al (2007(Brody et al ( , 2008a(Brody et al ( , 2009(Brody et al ( , 2010(Brody et al ( , 2011, Filipović et al (2012), Hughston and Macrina (2012), Macrina (2006), Mengütürk (2013), Rutkowski and Yu (2007)), gamma bridge information processes (Brody et al (2008b)), Lévy random bridge information processes (Hoyle (2010), Hoyle et al (2011Hoyle et al ( , 2015Hoyle et al ( , 2020, Mengütürk (2018)) and Markov bridge information processes (Macrina (2019)). In what follows we present a new model for the market filtration, based on the variance-gamma process.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting models are finely tuned to the structures of the assets that they represent, and therefore offer scope for a useful approach to financial risk management. In previous work on information-based asset pricing, where precise definitions can be found that expand upon the ideas summarized above, such models have been constructed using Brownian bridge information processes (Brody et al (2007(Brody et al ( , 2008a(Brody et al ( , 2009(Brody et al ( , 2010(Brody et al ( , 2011, Filipović et al (2012), Hughston and Macrina (2012), Macrina (2006), Mengütürk (2013), Rutkowski and Yu (2007)), gamma bridge information processes (Brody et al (2008b)), Lévy random bridge information processes (Hoyle (2010), Hoyle et al (2011Hoyle et al ( , 2015Hoyle et al ( , 2020, Mengütürk (2018)) and Markov bridge information processes (Macrina (2019)). In what follows we present a new model for the market filtration, based on the variance-gamma process.…”
Section: Introductionmentioning
confidence: 99%